2004
DOI: 10.1007/s00253-003-1547-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced secretion of Bacillus stearothermophilus L1 lipase in Saccharomyces cerevisiae by translational fusion to cellulose-binding domain

Abstract: The secretion of Bacillus stearothermophilus L1 lipase in Saccharomyces cerevisiae was investigated by employing a fusion partner, a cellulose-binding domain (CBD) from Trichoderma harzianum endoglucanase II (THEG). The CBD was connected to the N-terminal of L1 lipase through an endogenous linker peptide from THEG. The expression cassette for the fusion protein in S. cerevisiae was constructed using the alpha-amylase signal peptide and the galactose-inducible GAL10 promoter. Secretion of CBD-linker-L1 lipase b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 17 publications
0
15
1
Order By: Relevance
“…With yeast host cells, 25 to 30 mg protein g DCW Ϫ1 have been reported for Saccharomyces cerevisiae (1,7,25), while 2 to 4 mg protein g DCW Ϫ1 have been reported for Pichia pastoris (6,20). It is often the case that large differences in production levels are observed using the same host cell, presumably due to differences in promoters, culture conditions, and the protein being expressed.…”
Section: Vol 77 2011 T Kodakarensis Gene Expression and Protein Sementioning
confidence: 98%
“…With yeast host cells, 25 to 30 mg protein g DCW Ϫ1 have been reported for Saccharomyces cerevisiae (1,7,25), while 2 to 4 mg protein g DCW Ϫ1 have been reported for Pichia pastoris (6,20). It is often the case that large differences in production levels are observed using the same host cell, presumably due to differences in promoters, culture conditions, and the protein being expressed.…”
Section: Vol 77 2011 T Kodakarensis Gene Expression and Protein Sementioning
confidence: 98%
“…The technology is based on genetically linking a short peptide or small protein domain to either the aminoor carboxy-terminus of the target protein and then using the fusion tag to facilitate efficient capture and purification of the chimeric protein on an affinity matrix. Certain fusion partners such as the maltose binding protein (MBP) (di Guan et al, 1988), carbohydrate binding modules (CBMs) (Ahn et al, 2004;Murashima et al, 2003), thioredoxin (Trx) (LaVallie et al, 1993), and the Escherichia coli protein N-utilizing substance A (NusA) (Davis et al, 1999), have been shown to improve product solubility and expression by stabilizing the mRNA (Makrides, 1996) or by providing a psuedo-chaperone effect (Samuelsson et al, 1994). Fusion tags have also been used to increase in vivo proteolytic stability (Jansson et al, 1990;Martinez et al, 1995;Staahl and Nygren, 1997), to serve as effective expression and localization reporters (Gerdes and Kaether, 1996;Ozawa, 2006), and, when combined with their corresponding leader peptide, to control product localization in or secretion from the expression host (Ford et al, 1991;Johnson et al, 1992;Uhlen and Moks, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that a CBM serving as a fusion partner may have additional values. In the expression of CBM-lipase fusion protein in yeast, for example, it was shown that CBM also enhanced secretion (1).…”
Section: Bioprocessingmentioning
confidence: 99%